2018
DOI: 10.1111/aogs.13281
|View full text |Cite
|
Sign up to set email alerts
|

Treatment‐related psychological stress in different in vitro fertilization therapies with and without gonadotropin stimulation

Abstract: Factors other than just pregnancy rate seem to have an impact on psychological stress in IVF treatment. Due to reduced psychological stress in NC-IVF, this treatment could be especially considered in psychologically stressed women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…In our systematic review, we found that patients receiving ovarian stimulation with GnRH antagonists had increased depressive symptoms compared to patients who did not receive ovarian stimulation (32). One study suggested that treatment with one GnRH agonist, buserelin, had a poorer mood profile than other GnRH agonist (goserelin) 1 week later but showed similar mood changes at the end of the trial (37).…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…In our systematic review, we found that patients receiving ovarian stimulation with GnRH antagonists had increased depressive symptoms compared to patients who did not receive ovarian stimulation (32). One study suggested that treatment with one GnRH agonist, buserelin, had a poorer mood profile than other GnRH agonist (goserelin) 1 week later but showed similar mood changes at the end of the trial (37).…”
Section: Discussionmentioning
confidence: 90%
“…When focusing on hormonal compounds other than GnRH agonists or antagonists, one recent trial has been developed to study the effect of clomiphene citrate on women under the IVF protocol (39). Moreover, in the study by Haemmerli Keller et al (32), patients under the protocol without gonadotropin stimulation could receive low doses of clomiphene (32). This latter study suggests that the lack of gonadotropin stimulation is associated with fewer changes in mood, as the effect size was very small (g = -0.07).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations